More Real Than Ideal: Household and Community Diversity at Metapontum, South Italy - Cabaniss, Andrew H. F. (Frontiers in Digital Humanities, 2019)
Empirical studies of ancient cities must break down communities into their component parts, but frequently encounter difficulty with the scarcity of excavated domestic structures (e.g. Kramer 1982, 673). I introduce to the archaeological literature the entropy estimating statistical bootstrap (EESB), a tool developed in information theory and computational social science by DeDeo et al. (2013) which provides a way to assess how representative a small dataset is of a parent population, categorized according to some useful typology. This method can be used to decide when small datasets can add further detail to our quantitative studies of archaeological settlements or when they need to be rejected as too small. I then illustrate its uses within the context of urban demography by examining the distribution of house forms to calculate household characteristics specific to Metapontum, an ancient Greek city. Future applications will include building larger urban datasets that are empirically grounded in the specific evidence for each community, facilitating the work of research programs such as urban scaling.